ダイ 23 ジ ナンキョク チイキ カンソク タイ ナツタイ ホウコク 1981-1982 - 前, 晋爾; マエ, シンジ; Mae, Shinji (1983)
P(論文) 第23次南極地域観測隊の夏期行動の概要を述べる。南極観測船「ふじ」は約500tの観測資材を積み, 1981年11月25日東京港を出港した。観測隊長兼越冬隊長星合孝男以下44名, うち前副隊長以下10名の夏隊員を含んでいる。さらにオブザーバー1名が乗船した。1981年12月11日オーストラリアのフリーマントル港に入港, 南極条約に基づくオーストラリア人交換科学者G. A. DUFFが乗船し, フリーマントル出港後生物調査を開始した。1982年1月4日, 昭和基地北方約50海里地点から第1便が昭和基地に飛び, その後劣悪な氷状のため, 1月19日まで定着氷に入れず, 空輸は難航した。1月19日以降昭和基地北方21海里地点より連続空輸を実施, 2月5日に完了した。その間, 新発電棟基礎工事, リュツォ・ホルム湾沿岸の地学調査や測地作業, 昭和基地における生物, 氷上における海洋調査, 各種観測装置の更新などを実施した。また, 2月1日第23次越冬隊は, 第22次越冬隊より昭和基地での業務を引き継いだ。2月11日「ふじ」は反転北上し, 2月14日, 15日にマラジョージナヤ基地にて地学・生物調査および超高層関係資料の回収を行い, さらに東方アムンゼン湾に向かった。2月16日から18日まで, エンダビーランドのリーセルラルセン山麓で地学・生物調査を実施し, 岩石, コケの採集を行った。その後海洋調査を実施しつつ北上, 3月12日モーリシャスのポートルイスに入港し, 第22次越冬隊および交換科学者G. A. DUFFは下船した。ポートルイス出港後, シンガポールを経由し, 4月20日東京港に入港した。 This report outlines the summer activities of the 23rd Japanese Antarctic Research Expedition (JARE-23) in 1981-1982. JARE-23 comprised 34 wintering persons led by Dr. Takao HOSHIAI and 10 men of the summer party led by the present author. A Japanese observer participated in the summer activities. An Australian exchange scientist under the Antarctic Treaty provisions, Mr. G. A. DUFF, jointed the summer party between Fremantle, Australia and Port Louis, Mauritius. The relief ship, icebreaker FUJI, left Tokyo on November 25,1981,carrying about 500 tons of cargo. After calling at Fremantle between December 11 and 16,she arrived at the edge of pack ice on December 31,1981. The transportation of cargo and personnel to and from Syowa Station was carried out between January 4 and February 11,1982. After the accomplishment of field operations in the Syowa Station area, FUJI visited Molodezhnaya Station and Amundsen Bay. Then she returned to Tokyo on April 20,1982 via Port Louis (March 11 to 17) and Singapore (April 1 to 8). The observation of ionosphere and the studies on the physical, chemical and biological oceanography were performed on board. At Syowa Station, studies on moss ecology and oceanographical observations in the ice-covered sea were carried out. Geological and geodetic surveys were made in the ice-free ...